2006
DOI: 10.1539/joh.48.124
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Heme Oxygenase‐1 in the Lungs of Rats Exposed to Crystalline Silica

Abstract: Expression of Heme Oxygenase-1 in the Lungs of Rats Exposed to Crystalline Silica: Hiroko NAGATOMO, et al. Department of Occupational Pneumology, Institute of Industrial and Ecological Sciences, University of Occupational and Environmental Health-Oxidative stress is thought to be the pathogenesis of pulmonary fibrosis induced by particles, and heme oxygenase-1 (HO-1) protects lung tissue against oxidative stress. We hypothesized that HO-1 is also associated with oxidative lung injury caused by exposure to part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
(23 reference statements)
1
13
0
Order By: Relevance
“…Therefore, the expression of protein (concentration of HO-1 protein / protein exactly) was increased from the acute phase as an acute inflammatory reaction. We have also reported that more alveolar macrophages were stained for HO-1 in rats exposed to crocidolite, chrysotile and crystalline silica compared with the control groups [7][8][9] . Maestrelli et al reported that HO-1-positive macrophages were increased in smokers with chronic obstructive pulmonary disease (COPD) as compared with nonsmoking subjects in an immunohistochemistry study of human lung surgical specimens 13) .…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Therefore, the expression of protein (concentration of HO-1 protein / protein exactly) was increased from the acute phase as an acute inflammatory reaction. We have also reported that more alveolar macrophages were stained for HO-1 in rats exposed to crocidolite, chrysotile and crystalline silica compared with the control groups [7][8][9] . Maestrelli et al reported that HO-1-positive macrophages were increased in smokers with chronic obstructive pulmonary disease (COPD) as compared with nonsmoking subjects in an immunohistochemistry study of human lung surgical specimens 13) .…”
Section: Discussionmentioning
confidence: 57%
“…Nagatomo et al examined HO-1 gene expression in animal lung tissue from 3 days to 3 mo after intratracheal instillation of crocidolite and reported a persistent increase in HO-1 gene protein expression 7) . Similar intratracheal instillations of crystalline silica, fine silica and chrysotile showed increased HO-1 gene protein expression in both the acute and chronic phases 8,9) . These findings reveal that asbestos and crystalline silica, which are hazardous to the lung, significantly and persistently increased the HO-1 protein expression.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our previous study using crystalline silica showed that even if the particles are of the same chemical composition, their biological effects vary depending on their particle size 4) . Hazard assessment of newly-generated respirable particles must therefore be conducted for such differences and various biomarker studies are currently being implemented to objectively and quantitatively assess the hazards of such substances [5][6][7][8][9][10][11][12][13][14] .…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Simultaneously, anti-oxidative responses such as production of glutathione and expression of heme oxygenase-1 (HO-1) are activated 17,18) . Inhalation of asbestos and crystalline silica induce severe oxidative stress and subsequent expression of HO-1 19,20) . Detection of the level of oxidative stress is an important factor in forecasting a disease.…”
mentioning
confidence: 99%